PERISTILAHAN BEJADI (UPACARA ADAT PERKAWINAN) MASYARAKAT DAYAK SAWE DI KECAMATAN SEKADAU HULU KABUPATEN SEKADAU - Asit, Teresia; Simanjuntak, Hotma; Heryana, Nanang (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
Language is a tool used by humans to communicate. Language is neverseparated from humans, and vice versa, customs are no exception.Even language is an object that connects the function and meaning ofthese customs. Now many young people don't care about customs,especially preserving traditional marriage ceremonies. Therefore,researchers examined the Dayak sawe marriage customs, commonlycalled Bejadi, so that the younger generation can see how unique andrich the culture and language used are. This study uses a descriptivemethod in the form of qualitative research, which aims to describe theresults of the form of the term Bejadi, the lexical, grammatical, andcultural meanings of Bejadi, as well as the implementation of theterminology of Bejadi in learning Indonesian at school. The datasource used in this study is the primary data source because it wasobtained through direct interviews with informants who are directlyrelated to the location of the object under study, namely in SekadauHulu District, Sekadau Regency. The source of the data obtained isfrom the bejadi event (traditional wedding ceremony) using the DayakSawe language. The results of this study were analyzed based on theirform so as to produce monomorphemic terminology, polymorphemic(affixations, suffixes, reduplications, and compound words), as well asphrases. From these data it can also generate the meanings that existin Bejadi, namely lexical meanings, grammatical meanings, andcultural meanings. Data acquisition was obtained based on theprocession, actors involved, tools, and materials at the event.